1972
DOI: 10.1159/000230818
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Carcinoembryonic Antigen

Abstract: The presence of carcinoembryonic antigen (CEA) in saline extracts (SE) prepared from adenocarcinomas of the colon has been confirmed. This antigen was also detected in perchloric acid extracts (PAE) and in boiled and ethanol precipitated extracts (BE) of colonic tumors. CEA was present in BE preparations of feces from 4 of 8 patients with colon cancer. None of the feces BE specimens from 7 normal individuals contained detectable CEA. In addition, CEA was detected in PAE of sputum from patients with cystic fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1973
1973
1993
1993

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Subsequently, CEA was demonstrated in a variety of nonintestinal neoplasms and in certain nonmalignant diseases [2,3], as well as in normal adult tissues, in low concentration [4][5][6]. CEA is now classified as one of the tumor-associated antigens (TAA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, CEA was demonstrated in a variety of nonintestinal neoplasms and in certain nonmalignant diseases [2,3], as well as in normal adult tissues, in low concentration [4][5][6]. CEA is now classified as one of the tumor-associated antigens (TAA).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data have been pre sented at national meetings [ 14,15]. The tumors were propagated by injecting weanling Fischer rats under the skin of the back with 108 viable tumor cells suspended in Medium 199 containing penicillin and streptomycin.…”
Section: Introductionmentioning
confidence: 99%
“…For con trols, sera of 100 blood donors and 24 healthy staff members of this department were included; they too gave negative results. Perchloric acid extracts (PAE) [5] of 12 cancer tissues and saline extracts (SE) of 11 lymphoma-leukemia spleen specimens ob tained at 100 C were also examined. PAE of 3 cancer tissues and SE of 2 spleens gave positive results in agglutination-inhibition tests.…”
mentioning
confidence: 99%
“…However, specificity for the diagnosis of tuberculosis should be solved [9], Classically, PCA was used for the extraction of glyco protein from samples. Carcinoembryonic antigen was de tected in PCA extracts of colonic tumors [24], Kim et al [13] found that after the extraction of biological specimens with PCA, the IgG or its fragments demonstrable by ELISA in the original preparations which might elicit pos itive reactions in control wells were not demonstrated in the extracts.…”
Section: Discussionmentioning
confidence: 99%